DEVELOPMENT OF THE MOBILE CAP LEARNING MODEL IN HIGH SCHOOL FOR CIVICS SUBJECT - Khairil Anwar Uzir; Sahat Siagian; R. Mursid (RADJA PUBLIKA, 2025)
Abstract: The purpose of this study is to (1) find out the Mobile CAP learning model is suitable for use in Civics Subject learning, (2) find out the Mobile CAP learning model is practically used in Civics Subject learning, (3) find out that the Mobile CAP model is effective in Civics Subject learning in Class X of Pematangsiantar City High School. The development procedure of the Mobile CAP model refers to the Plomp development model accompanied by several modifications by paying attention to the R&D research steps consisting of the initial investigation phase, the design phase, the realization phase, the testing phase, evaluation, and revision. The location of the development trial is SMA Negeri 6 Pematangsiantar. The results of the study, namely the assessment or feasibility measurement carried out by experts on the learning model and supporting device products in the form of learning models, model books, teacher manuals, student manuals, Mobile CAP media, and the evaluation of learning outcomes as a whole are valid/feasible to be used for Civics Subject learning to students. The results of the practicality test through observation of teacher and student activities during learning, one-on-one trials, limited group trials, and field trials conducted on teachers and students prove that the entire product developed is very practical to use for Civics Subject learning for students. The results of the product effectiveness test through student learning outcomes obtained an N-Gain price with a high category which means that the product developed is effectively used in the implementation of Civics Subject learning for students.